Pengaruh Efikasi Diri (Self Efficacy) terhadap Kemampuan Pemecahan Masalah Matematika - Ipah Kholivah; Huri Suhendri; Leonard Leonard (EduResearch Mitra Inovasi, 2020)
The purpose from this research is to know self-efficacy influence toward student ability of mathematic problem solving. This research uses survey as the method. The population in this research consists of 181 students. This research is done by using questionnaires and tests with the total of the sample are 65 students. The sampling technique is done randomly and proportionally stratified (Proportionate Stratified Random Sampling). Data measurement and collection of student ability of mathematic problem solving use a written instrument like essay. Previously, the instrument was already tested in validity, reliability, difficulty level and distinguished tests ability so thereafter, data analysis requirement test is also conducted. Based on research hypothetical test, the result is t calculation > t table, which is 2,49 > 1,998 so H1 is accepted and H0 is rejected. The conclusion is there is an influence from self-efficacy towards toward student ability of mathematic problem solving.